Philosophy and psychology: Once again together? - Braun, Ricardo (2005)
The relationship between philosophy and psychology in the history of contemporary psychology is examined, pointing out the outstanding coincidence of topics and worries found in the philosophy of mind and theoretical psychology. Psychoanalysis has also been a subject of philosophical interest, not only theoretical presuppositions of psychoanalysis but its methodology in relation to other sciences as well. Nowadays, unity between psychology and philosophy together with other disciplines, has been achieved in cognitive science.